Five new species of Homoscleromorpha (Porifera) from the Caribbean Sea and re-description of Plakina jamaicensis. (10th April 2013) - Ereskovsky, Alexander V.; Lavrov, Dennis V.; Willenz, Philippe
Abstract : Five new species of Homoscleromorpha (Porifera) of four genera, Oscarella, Plakortis, Plakina and Corticium, are described from vertical walls of reef caves at depths ranging from 23 to 28 m in the Caribbean Sea. Oscarella nathaliae sp. nov. has a leaf-like thinly encrusting, flat body, loosely attached to the substrate and a perforated, not lobate surface. Oscarella nathaliae sp. nov. contains two bacterial morphotypes and is characterized by two mesohylar cell types with inclusions. Plakortis myrae sp. nov. has diods of two categories: abundant large ones (83–119 μm long) and rare small ones (67–71 μm long) with sinuous, S-bent centres; triods Y- or T-shaped (18–5  μm long), and abundant microrhabds (5–12 μm long). Plakortis edwardsi sp. nov. has diods of one category with thick, sinuous, S-bent centres (110 to 128 μm long); triods T-shaped (actines 28–59 μm long). It is the only species of this genus showing small diods (22–31 μm long). Plakortis dariae sp. nov. has diods of two categories: large ones (67–112 μm long) and small, rare, irregular ones, slightly curved, often deformed with one end blunt (30–59 μm long); triods rare and regular (actines 20–44 μm long). Corticium diamantense sp. nov. has oscula situated near its border, regular non-lophose calthrops of one size-class, very rare tetralophose calthrops and candelabra with the fourth actine ramified basally in 4–5 microspined rays. In addition, a re-description of Plakina jamaicensis is based on newly collected material and the type specimen. Plakortis jamaicensis has a convoluted brain-like surface; well developed sub-ectosomal cavities; irregular sinuous diods, triods, calthrops, rare monolophose calthrops, rare dilophose calthrops, rare trilophose calthrops and common tetralophose calthrops. Molecular 'barcoding' sequences for mitochondrial cob are given for Plakortis edwardsi sp. nov., P. dariae sp. nov., Plakina jamaicensis and Corticium diamantense sp. nov. An identification key for all western Atlantic Homoscleromorpha is provided.